The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the Proceedings of the 1st Asian Conference on Humanities, Industry, and Technology for Society, ACHITS 2019, 30 2019
DOI: 10.4108/eai.30-7-2019.2287551
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Compensation and Benefits Towards Employee Performance

Abstract: Nowadays, taking care the welfare of the employee is very important in order to ensure them to hard work in achieve the organizational goal. The aim of the study is to establish the effect of compensation and benefits towards employee performance. The objective of this research is firstly, to evaluate the level of employee performance. Secondly, this research aims to examine the relationship between compensation and benefits towards employee performance. Lastly, determine the effect of the compensation and ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Furthermore, the findings of this study were that salary and allowance and social security have nominal effect on employee's performance in insurance companies in Nepal. This result is contradicted with the result of Kadir et al, (2019) However, social security and salary and allowance have strong impact on performance of employees in every organization.…”
Section: Regression Analysismentioning
confidence: 86%
“…Furthermore, the findings of this study were that salary and allowance and social security have nominal effect on employee's performance in insurance companies in Nepal. This result is contradicted with the result of Kadir et al, (2019) However, social security and salary and allowance have strong impact on performance of employees in every organization.…”
Section: Regression Analysismentioning
confidence: 86%
“…While benefits typically refer to health life insurance, disability insurance, retirement plans, vacation, and so on (Odunlade, 2012). Besides, benefits are indirect financial and non-financial payments that employees receive because of their employment with the organization (Kadir, AlHosani, & Fadillah Ismail, 2019). Feraro-Banta and Shaikh (2017) reported that low benefits would lead to low satisfaction increasing employee absenteeism.…”
Section: Salary and Benefits And Well-beingmentioning
confidence: 99%
“…Based on previous research, this study hypothesizes that compensation and benefits have a favorable impact on work performance, and compensation and benefits are proven to be a major predictor of job performance (Akter & Husain, 2016;Darma & Supriyanto, 2017;Dayanandan, 2017;Fulmer & Li, 2022;Kadir et al, 2019). For example, according to the findings of Aktar, Sachu, and Ali (2012)'s research involving 180 employees from 12 commercial banks in Bangladesh, reward plays a major role in motivating employees to perform their tasks better so that they can contribute and produce too many opinions which can enhance organizational performance in the form of monetary and non-monetary benefits as there is a positive relationship.…”
Section: Compensation and Benefitsmentioning
confidence: 99%